The Semantics and Ethics of Sa‘ādah (Happiness) in the Qur’ān - El-Zeiny, Iman (Islamic Studies, 2020)
A great deal of Arabic and English literature has been written on the Arabic term sa‘ādah (happiness) from a philosophical perspective. However, this paper explores the semantic-statistical role of the term sa‘ādah in the Qur’ān as a constituent of the Islamic ethical discourse that shapes the mentalities of Muslims, in order to establish successful communication with other communities through grasping the Muslim worldview. Ethical systems are rooted in particular worldviews. The ethical foundation of Islamic thought is based on the Qur’ānic ethical discourse, which is built upon fundamental concepts such as sa‘ādah. The model of semantic analysis developed by Toshihiko Izutsu (d. 1993) has been adopted to analyze the concept sa‘ādah in this paper. This model of semantic analysis aims at discovering the worldview conceptualized by the people who use that language through identifying its “basic meaning” (i.e., etymological meaning) and “relational meaning” (i.e., co-textual and contextual meanings). The statistical analysis given in this paper is based on Kais Dukes’ analysis.